Pengembangan Strategi Komunikasi Digital Berkelanjutan untuk Pemberdayaan Ekonomi Desa Wisata Papoh, Kabupaten Blitar - Fitri Norhabiba; Vinda Maya Setianingrum; Puspita Sari Sukardani; Anam Miftakhul Huda; Hasna Nur Lina; Teguh Dwi Putranto (Journal of Indonesian Society Empowerment, 2026)
This community service activity was carried out to strengthen the digital communication and branding capacity of Papoh Tourism Village, Sukosewu Village, Gandusari District, Blitar Regency. The partners' main problems included the sub-optimal destination communication strategy, limited social media management skills, lack of understanding in tourism storytelling, and the unavailability of sustainable promotional communication guidelines. The activity method used a participatory approach through needs analysis, training, content production practices, assistance in preparing content calendars, as well as monitoring and evaluation. The activity participants consisted of tourism village managers, Pokdarwis (Tourism Awareness Group), Karang Taruna (Youth Organization), and local MSME actors. The results of the activity showed that participants were able to identify the uniqueness of Papoh Tourism Village, formulate key destination messages, compile promotional narratives, and produce photo content, short videos, and social media captions based on local potential. The assistance also resulted in a digital communication strategy draft that can be used as a guide for managing tourism village promotions. This activity confirms that branding strengthening activities play an important role in increasing destination visibility, strengthening the tourism village image, and supporting the economic empowerment of the local community. program sustainability requires management commitment, publication consistency, and periodic evaluation of digital audience responses. Kegiatan pengabdian kepada masyarakat ini dilaksanakan untuk memperkuat kapasitas komunikasi digital dan branding Desa Wisata Papoh, Desa Sukosewu, Kecamatan Gandusari, Kabupaten Blitar. Permasalahan utama mitra meliputi belum optimalnya strategi komunikasi destinasi, keterbatasan keterampilan pengelolaan media sosial, minimnya pemahaman storytelling wisata, dan belum tersedianya panduan komunikasi promosi yang berkelanjutan. Metode kegiatan menggunakan pendekatan partisipatif melalui analisis kebutuhan, pelatihan, praktik produksi konten, pendampingan penyusunan kalender konten, serta monitoring dan evaluasi. Peserta kegiatan terdiri atas pengelola desa wisata, Pokdarwis, Karang Taruna, dan pelaku UMKM lokal. Hasil kegiatan menunjukkan bahwa peserta mampu mengidentifikasi keunikan Desa Wisata Papoh, merumuskan pesan kunci destinasi, menyusun narasi promosi, serta memproduksi konten foto, video singkat, dan caption media sosial berbasis potensi lokal. Pendampingan juga menghasilkan rancangan strategi komunikasi digital yang dapat digunakan sebagai panduan pengelolaan promosi desa wisata. Kegiatan ini menegaskan bahwa kegiatan penguatan branding berperan penting dalam meningkatkan visibilitas destinasi, memperkuat citra desa wisata, dan mendukung pemberdayaan ekonomi masyarakat lokal. Keberlanjutan program memerlukan komitmen pengelola, konsistensi publikasi, dan evaluasi berkala terhadap respons audiens digital.